(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
The study was conducted among 946 women attending antenatal clinic in SMIMER teaching hospital during 2008 to know their awareness regarding various aspects of mother-to-child transmission (MTCT) of HIV and it was found that though the general awareness of HIV is high, awareness of MTCT and its prevention is low which need to be improved through focused IEC campaign. Background : More than 90% of HIV infections in children aged <15 years are due to mother-to-child transmission (MTCT). The MTCT may reverse the gains of the child survival strategy in the country. Awareness of HIV and MTCT among antenatal women plays crucial role in preventing MTCT. Objective : To evaluate the awareness and knowledge of HIV/AIDS, MTCT of HIV and the methods to prevent MTCT of HIV. Methods : This is a descriptive cross sectional study carried out among antenatal women at the SMIMER Teaching Hospital during 2008. Results : Out of 946 women interviewed, 78% had heard of HIV/AIDS and main sources of information were television (48.8%) and radio (37.8%). Ninety-one percent of women were aware of MTCT of HIV. Trans-placental route (41%) was the commonly identified route of transmission. Awareness of HIV/AIDS, HIV co-existence with pregnancy and Mother to child transmission was significantly higher among women with at least secondary education (P<0.05). The level of knowledge and perceptions of MTCT of HIV is inadequate. Conclusion : There is an urgent need to scale up HIV awareness programme focusing on mother-to-child transmission in the region. Keywords: Awareness; education; mother-to-child transmission; prevention; HIV DOI: 10.3126/saarctb.v7i1.3956 SAARC J. TUBER. LUNG DIS. HIV/AIDS 2010 VII(1) 8-12